2015
DOI: 10.1002/ejic.201403225
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Iron(III) Complexes as Functional Models of Catechol Oxidases and Catalases

Abstract: Mononuclear amino triphenolate iron(III) complexes have been synthesized and characterized (UV/Vis spectroscopy, cyclic voltammetry, ESI-MS, 1H NMR spectroscopy, X-ray diffraction). These complexes act as biomimetic catalysts promoting the aerobic auto-oxidation of 3,5-di-tert-butylcatechol to the corresponding o-benzoquinone at room temperature and displaying catalase activity for the hydrogen peroxide dismutation with remarkable activity (TON up to 4000)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Successful catalysts for cyclic organic carbonate (COC) formation include the use of abundant main-group metals such as aluminum, iron, and zinc and transition metals (Co, Cr), most often in combination with N x , O y -coordinating ligands such as salens ( x = y = 2) and aminotriphenolates ( x = 1, y = 3) . We have been interested in the use of O 3 N -chelating aminotriphenolate ligands and their complexes for catalytic applications and have reported on the use of Ti­(IV) derivatives for the oxidation of sulfides and secondary amines into nitrones, Mo­(VI) and W­(VI) complexes for the oxidation of sulfides, olefins and chloro- and bromoperoxidation, and more recently the Fe­(III)-mediated formation of cyclic carbonates and the preparation of catechol oxidase and catalase mimics . The use of aminophenolate type ligands is beneficial toward the stabilization of different (higher) oxidation states such as V­(III) and V­(V), and the V­(V) complexes have previously been successfully used in the context of haloperoxidase models in sulfoxidation chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Successful catalysts for cyclic organic carbonate (COC) formation include the use of abundant main-group metals such as aluminum, iron, and zinc and transition metals (Co, Cr), most often in combination with N x , O y -coordinating ligands such as salens ( x = y = 2) and aminotriphenolates ( x = 1, y = 3) . We have been interested in the use of O 3 N -chelating aminotriphenolate ligands and their complexes for catalytic applications and have reported on the use of Ti­(IV) derivatives for the oxidation of sulfides and secondary amines into nitrones, Mo­(VI) and W­(VI) complexes for the oxidation of sulfides, olefins and chloro- and bromoperoxidation, and more recently the Fe­(III)-mediated formation of cyclic carbonates and the preparation of catechol oxidase and catalase mimics . The use of aminophenolate type ligands is beneficial toward the stabilization of different (higher) oxidation states such as V­(III) and V­(V), and the V­(V) complexes have previously been successfully used in the context of haloperoxidase models in sulfoxidation chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…The representative spectral profiles obtained by the stoppedfollow technique (Fig. [12][13][14][15] show that the first step is fast and the second step is slow. These spectral features in Fig.…”
Section: Cyclic Voltammetry Measurementsmentioning
confidence: 98%
“…6 Oxidation mimicking studies using iron(III) complexes showed selective catalytic oxidation of catechol because it oxidized catechol to ortho quinone instead of ring-breaking. [7][8][9][10][11][12][13][14][15] Several studies have reported the catalytic activity of iron complexes for the selective oxidation of o-aminophenols to produce the pharmaceutically important amino-3-H-phenoxazin-3-one (APX) instead of ring-opening. [16][17][18][19][20][21][22][23][24] The current study aims to gain a deeper understanding of the natural process of metal ions as catalysts and gain experience in designing more efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we reported about the use of tetradentate metal complexes in catalysis, molecular recognition, and as molecular scaffolds for multiple functionalization. Among the different structures, μ-oxo dinuclear titanium complex 1 represents the ideal architecture to become a scaffold for multiple functionalization (Scheme ).…”
Section: Introductionmentioning
confidence: 99%